Avaliação das sub-frações dos carboidratos e das proteínas, usando as metodologias do CNCPS e in situ corn bovinos da raça Nelore. 2. Milho e farelo de algodão - Pereira, João Ricardo Alves [UNESP]; Vleira Bose, Max Lázaro; Boin, Celso (My University, 1997)
The chemical composition of corn and cottonseed meal was determined in accordance with the Cornell Net Carbohydrate and Protein System (CNCPS) in diets with forage:concentrate ratios of 80:20 (D1) and 60:40 (D2) using Nellore cattle. The potential and effective degradabilities of the carbohydrate and protein subfractions were also determined. For corn, diet 2 resulted in an increase for potentially degradable dry matter (DM). An increase was observed in the effective degradation of DM (EDDM) when lag time was not considered, however, the use of lag time increased the EDDM for both diets, 23 and 18% for D1 and D2, respectively. For cottonseed meal, diet 2 determined a reduction in the potentially degradable DM; therefore, the use of lag time increased the EDDM for both diets, 14% for D1 and 15% for D2. The availability of corn starch (fraction B1) was lower than that determined by CNCPS. The higher values for the degradability of corn and cottonseed meal protein subfractions may indicate an underestimation by the model, and, or, could be attributed to the Zebu animals used in this study.
Evaluation of the carbohydrate and protein subfractions, using CNCPS and in situ methodologies with Nellore cattle. 2. Corn and cottonseed meal
Keywords: Carbohydrate; Corn; Cottonseed meal; Degradability; Nellore; Protein